Pengaruh Pola Asuh Islami terhadap Kecerdasan Moral Anak Akhir di Desa Umbul Kedungjajang Lumajang - Tiningsih, Saniatun (Fakultas Dakwah UIN KHAS Jember, 2024)
Parents are the main role takers in caring for their children. Attitudes towards parenting are reflected in different parenting patterns for children because parents and families have certain parenting patterns. It is not uncommon to find that parents must be able to provide guidance, direction, or implement education that can make children carry out Islamic teachings correctly and make children have good morals. And prepare their children to become a young generation who have morals that refer to Islamic norms. The aim of this research is: To determine the influence of Islamic parenting on the moral intelligence of final children in Umbul Kedungjajang Village, Lumajang. This research uses quantitative research methods, with data collection methods through observation, interviews and distributing questionnaires. The data analysis method used is a simple linear regression analysis test, hypothesis testing using the f test and t test. The population in this study included all final children (aged 6-12 years) in the entire TPQ of Umbul Kedungjajang Lumajang village, and a sample of 15 students were drawn. The sampling technique used was purposive sampling. Data processing uses the SPSS 17 application. The results of this study show that overall there is no influence of Islamic parenting on children's moral intelligence. It can be seen that the R square gain in the summary model of linear regression analysis is .001 or 0.1%. This means that the child's moral intelligence explained is 0.1%, while the remaining 99.% is influenced by other variables outside this research. Thus, the data collected failed to prove the research hypothesis with a contribution of ninety-nine percent. Thus, this can be interpreted that the moral intelligence of children in Umbul village is not significantly influenced by Islamic parenting. Thus, predictions of variables that influence children's moral intelligence in Umbul Village include: peers, school environment, community environment, personality, and religious education.